2010
DOI: 10.4028/www.scientific.net/jbbte.8.45
|View full text |Cite
|
Sign up to set email alerts
|

Prospects and Pits on the Path of Biomimetics: The Case of Tooth Enamel

Abstract: This review presents a discourse on challenges in understanding and imitating the process of amelogenesis in vitro on the molecular scale. In light of the analysis of imitation of the growth of dental enamel, it also impends on the prospects and potential drawbacks of the biomimetic approach in general. As the formation of enamel proceeds with the protein matrix guiding the crystal growth, while at the same time conducting its own degradation and removal, it is argued that three aspects of amelogenesis need to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 159 publications
(221 reference statements)
1
15
0
Order By: Relevance
“…Convenient for following the adsorption of species onto dispersed particles of interest, ζ potential analyses have also recently been used to detect binding of amelogenin nanospheres onto apatite crystals under various conditions [75] and correspondingly improve the understanding of the mechanism of amelogenesis, a biomineralization process during which a finely structured protein gel directs the growth of hierarchically ordered enamel crystals, the hardest material in the vertebrate body. [76] Finally, the brain itself, as a whole, has a specific ζ potential, which implies that the extracellular translational motion is governed by electrokinetic effects under this naturally occurring electric field in addition to diffusion and tissue tortuosity. [77] …”
Section: Other Applications Of the Concept Of ζ; Potential In Biochemmentioning
confidence: 99%
“…Convenient for following the adsorption of species onto dispersed particles of interest, ζ potential analyses have also recently been used to detect binding of amelogenin nanospheres onto apatite crystals under various conditions [75] and correspondingly improve the understanding of the mechanism of amelogenesis, a biomineralization process during which a finely structured protein gel directs the growth of hierarchically ordered enamel crystals, the hardest material in the vertebrate body. [76] Finally, the brain itself, as a whole, has a specific ζ potential, which implies that the extracellular translational motion is governed by electrokinetic effects under this naturally occurring electric field in addition to diffusion and tissue tortuosity. [77] …”
Section: Other Applications Of the Concept Of ζ; Potential In Biochemmentioning
confidence: 99%
“…Secondly, its microstructure is dominated by parallel rods [1,2], composed of bundles of 40-60 nm wide apatite crystals with the aspect ratio of up to 1:10 4 . And thirdly, it is the most mineralized tissue in the human body, comprising 96-98 wt% of the mineral phase, apatite, which is best described by the stoichiometric formula (Ca,Z) 10 (PO 4 ,Y) 6 (OH,X) 2 , where Z¼Na + , Mg 2 + , K + , Sr 2 + , etc., Y ¼CO 3 2 À , HPO 4 2 À and X¼Cl À , F À . The microstructural and morphological difference of apatite crystals in enamel compared to those present in bone and dentin have suggested that the mechanism of formation of apatite crystals in enamel may be markedly different from the organic-template-based one associated with collagenous hard tissues, such as bone or dentin [3].…”
Section: Introductionmentioning
confidence: 99%
“…This is illustrated in Fig.1, where two HAp crystals of geological origin are shown: one with the exposed (001) face by cutting and the other one with diagonal (011) and (101) faces instead of (001), the result of the sole directional growth of (001). An example among apatites of biomineral origin comes from the tooth enamel, where HAp grows almost uniaxially in the [001] direction, leading to the comparatively minor presence of basal, (001) faces in comparison with the prismatic, (hk0) ones in the final crystal forms 74 . The growth of HAp platelets (30 × 20 × 2 nm 75 ) in bone, however, proceeds in a very different manner.…”
Section: Peculiarities Of Hapmentioning
confidence: 99%